2023
DOI: 10.1007/s00405-023-07863-8
|View full text |Cite
|
Sign up to set email alerts
|

The risk of central nodal metastasis based on prognostic factors of the differentiated thyroid carcinoma: a systematic review and meta-analysis study

Abstract: Background and aim Despite improving the 10-year disease-free-survival, prophylactic central neck dissection (pCND) in differentiated thyroid carcinoma (DTC) should only be considered in patients with high risk factors for lymph node (LN) metastasis due to the increases in the risk of postoperative complications. Our aim was to identify the risk factors for central lymph node metastasis (CLNM) in DTC. Method We searched PubMed, Scopus, Web of science, Coch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…34 A systematic review and meta-analysis encompassing 27,741 patients from 41 studies indicated that age < 45 years and male gender were risk factors for central lymph node metastasis. 35 A 2010 study based on a Korean population found that tumor diameter >2 cm was significantly associated with lymph node metastasis, 36 while a 2012 Japanese study supported this finding, stating that tumor size (>2 cm) was the strongest predictor of microscopic central and lateral node metastasis in multivariate logistic analysis. Moreover, tumor size most markedly impacted DCA, and clinical impact curve, all the results indicated that the nomogram presenting a high accuracy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…34 A systematic review and meta-analysis encompassing 27,741 patients from 41 studies indicated that age < 45 years and male gender were risk factors for central lymph node metastasis. 35 A 2010 study based on a Korean population found that tumor diameter >2 cm was significantly associated with lymph node metastasis, 36 while a 2012 Japanese study supported this finding, stating that tumor size (>2 cm) was the strongest predictor of microscopic central and lateral node metastasis in multivariate logistic analysis. Moreover, tumor size most markedly impacted DCA, and clinical impact curve, all the results indicated that the nomogram presenting a high accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…A study from central China discovered that patients aged ≤18 years (OR = 4.41, p < 0.001) and 19–45 years (OR = 1.97, p = 0.002) had a higher risk of lateral LNM than patients aged >60 years 34 . A systematic review and meta‐analysis encompassing 27,741 patients from 41 studies indicated that age < 45 years and male gender were risk factors for central lymph node metastasis 35 . A 2010 study based on a Korean population found that tumor diameter >2 cm was significantly associated with lymph node metastasis, 36 while a 2012 Japanese study supported this finding, stating that tumor size (>2 cm) was the strongest predictor of microscopic central and lateral node metastasis in multivariate logistic analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The 2015 American Thyroid Association (ATA) guidelines recommend therapeutic central lymph node dissection (CLND) in patients with lymph node metastasis (LNM) ( 6 ), while prophylactic central lymph node remains controversial for patients with cN0. Several studies have reported significant improvements in 10-year disease survival and local area control in PTC with bilateral pCND followed by personalized radioiodine therapy ( 7 ). Furthermore, studies have indicated that performing pCND in stage clinical lymph node-negative (cN0) patients does not significantly reduce the risk of local recurrence.…”
Section: Introductionmentioning
confidence: 99%